Upaya Pasangan Tunanetra dalam Membentuk Keluarga Sakinah; Studi Kasus di Kecamatan Manggala, Kota Makassar - Haerul Haerul; Rahmatiah Rahmatiah HL (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
How are the efforts of a blind couple in forming a sakinah family at the Karya business foundation for the blind in forming a sakinah family in the blind works business foundation? 2) What are the obstacles that occur for blind couples in blind works business foundations? This type of research is field research that departs from observers and social fact finding which is studied using sociological, anthropological and normative juridical approaches.The results of this study indicate that 1) The efforts of blind couples in forming a sakinah family are influenced by the fulfillment of economic needs where the couples in fulfilling their economic needs trade or become medium masseurs services based on spiritual aspects where the efforts made are that through the foundation they get guidance. spiritual from the teaching staff 2) the obstacles for blind couples in forming a sakinah family, there are several things, including physical conditions that experience economic limitations which sometimes become obstacles to ineffective communication and disputes, and disputes that often occur in the household. 3) the family sakinah is a family that is calm, peaceful and happy physically and spiritually, this is an important aspect goal that must be built in the family and become a good goal before fostering a household and after determining the concept of happiness In life, the implications of this study include 1) This study discusses how blind couples are trying to form a sakinah family and also discusses the meaning of marriage. and the concept of the sakinah family which provides a reference and is also used as a reference material for further research 3) to the partner